Comparison of the Effects of Circuit Training and Fartlek on the Intermittent Endurance of Unsri United Soccer Players - Pratama, Reza Resah; Satria, M. Haris; Defliyanto, Defliyanto; Ramadhan, Arizky; Hidayat, Arif (Indonesian Journal of Physical Education and Sport Science, 2026)
Intermittent endurance is a crucial physical component in modern football because it is related to a player's ability to perform high-intensity activities repeatedly with short recovery times. Developing effective training methods to improve this capacity is a crucial requirement in the development of adolescent players. This study aims to analyze and compare the effects of circuit training and fartlek training on the intermittent endurance of Unsri United soccer players. This research method uses a quantitative approach with a quasi-experimental two-group pretest–posttest design. The study population was school soccer players aged 14–17 years, with a sample of 30 players divided into two treatment groups (15 people each). The measurement instrument used was the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1). Data analysis was carried out through normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and analysis of covariance with a significance level of 0.05. The results showed that both training methods provided significant improvements in intermittent endurance. However, the improvement achieved by the circuit group was statistically higher than that of the fartlek group, even after controlling for baseline scores. The effect size showed a strong practical impact, thus indicating the relevance of the training method to the physiological demands of soccer. Conclusion: Circuit training is more effective than fartlek training in improving intermittent endurance in adolescent soccer players. This study recommends the systematic implementation of circuit training programs in the preparatory phase of youth soccer development, and encourages further research with more rigorous experimental designs and additional physiological variables to enrich the scientific study of soccer coaching.